Early Gaya: The Emergence of Tirthasraddha - Sayers, Matthew R. (Religions of South Asia, 2017)
This article describes the earliest recognition of tirtha in the dharmasastra literature, discusses the earliest associations between tirtha and sraddha, and traces the emergence of Gaya as a sacred place with a particular connection to sraddha as found in the Brahmanical religious literature. I argue that the references to tirthasraddha and Gaya found in the earliest Brahmanical dharma texts represent fledgling efforts by the educated class of brahmins to appropriate and legitimate the ritual practices associated with pilgrimage by incorporating them into their discourse on dharma.